Ella. - Peet, Bill. (Boston, Houghton Mifflin, 1964)
A spiteful, conceited elephant runs away from the circus and immediately regrets her course of action.
Booklist
School Library Journal
Kirkus Reviews
4.3
K-3
Keywords: Elephants -- Fiction; Stories in rhyme; Elephants -- Fiction; Stories in rhyme